2-Thiobarbituric acid addition improves structural integrity and controlled drug delivery of biocompatible pectin hydrogels - BATIREL, SAİME (TAYLOR & FRANCIS AS, 2021)
Thiolated polymers are commonly preferred for biomedical applications with their good permeation properties providing them higher bioavailability. However, the thiolation process is mostly time-consuming series of chemical reactions. This study describes a simple irreversible thiol group integration to the pectin hydrogels by noncovalent bonding. We used 2-thiobarbituric acid (TBA) for thiolation. We proved with full-atom molecular dynamics simulations and experimental methods that TBA desertion is negligible. Pectin hydrogels become more flexible and their disintegration is delayed from 4 h up to four days with TBA addition. Also, hydrogels can successfully deliver the model drug, theophylline, showing a controlled release profile.
Keywords: Biopolymers; drug delivery systems; hydrogels; molecular dynamics; simulations; IN-VITRO EVALUATION; THIOLATED POLYMERS; CROSS-LINKING; SYSTEMS